Parasitological, Molecular, and Histopathological Investigation of the Potential Activity of Propolis and Wheat Germ Oil against Acute Toxoplasmosis in Mice - Ashraf Mohamed Barakat; Khaled A. Abd El-Razik; Hassan Ali Mohamed El Fadaly; Walaa M. Saleh; Fatma Abo Zakaib Ali; Asmaa Aboelabbas Gouda; Sabry A. S. Sadek; Naief Dahran; Manal F. El-khadragy; Ehab Kotb Elmahallawy (MDPI AG, 2023)
Toxoplasmosis is one of the most common parasitic zoonoses that affects all vertebrates. The drugs most commonly used against toxoplasmosis have many side effects, making the development of new antiparasitic drugs a big challenge. The present study evaluated the therapeutic effectiveness of novel herbal treatments, including propolis and wheat germ oil (WGO), against acute toxoplasmosis. A total of 50 albino mice were divided into five groups: group 1 (G1) (non-infected and non-treated); group 2 (G2) (infected without treatment); group 3 (G3) (treated with propolis); group 4 (G4) (treated with WGO); group 5 (G5) (treated with a combination of propolis and WGO). The effects of the herbal substances on different organs, mainly liver, spleen, and lungs, were investigated using parasitological, molecular, and histopathological examinations. The results of parasitological examination demonstrated statistically significant (p < 0.05) differences in the parasitic load between treated groups (G3, G4, and G5) compared to the control positive group (G2). These differences were represented by a significant reduction in the parasite load in stained tissue smears from the liver obtained from the animals treated with propolis (G3) compared to the parasite load in the positive control group. Similarly, animals (G4) treated with WGO exhibited a significant reduction in the parasite load versus the positive control group, while the lowest parasite load was found in G5, treated with propolis and WGO. Quantification of the parasite burden through molecular methods (PCR) revealed similar findings represented by reduction in the parasite burden in all treated groups with WGO and propolis as compared to the control group. Importantly, these previous parasitological and molecular findings were accompanied by a marked improvement in the histopathological picture of the liver, spleen, and lungs. In conclusion, propolis and WGO showed a good combination of therapeutic efficacy against acute toxoplasmosis.